(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the epidemiological, clinical, and laboratory characteristics of children with measles requiring intravenous immunoglobulin (IVIG) treatment at the Vietnam National Children’s Hospital from January to June 2025. Methods: A retrospective descriptive study was conducted on 111 patients under 18 years of age with confirmed measles diagnosis and IVIG indication, admitted to the Tropical Diseases Center, Vietnam National Children’s Hospital. Results: Children under 9 months of age accounted for 43.2% of the cohort. A total of 81.1% of patients were unvaccinated against measles, including 62.8% in the age-eligible group. Comorbidities were present in 55.9% of patients, predominantly chronic respiratory disease (28.8%) and immunodeficiency (12.6%). The most common clinical features were fever (98.2%), rash (89.2%), cough (69.4%), and conjunctivitis (65.8%). Cytokine storm was the most frequent severe complication (46.8%), followed by shock (21.6%) and rapidly progressive pneumonia (13.5%). Laboratory findings revealed significant organ involvement and systemic hyperinflammation, with mean LDH of 911.7 U/L, mean ferritin of 1,024.0 ng/mL (maximum 20,165 ng/mL), and mean D-dimer of 2,096.8 ng/mL. Conclusions: Pediatric patients with severe measles requiring IVIG at a tertiary referral center are characterized by young age, incomplete vaccination status, high rates of comorbidities, and severe multi-organ dysfunction. Strengthening timely vaccination, early case identification, and prompt therapeutic intervention are essential strategies to reduce the burden of severe measles in children.